Does bullying due to oral conditions influence cigarette smoking in adolescents? A structural equation modeling - Bruna BRONDANI; Jessica Klöckner KNORST; Bernardo Antonio AGOSTINI; Yassmín Hêllwaht RAMADAN; Fausto Medeiros MENDES; Thiago Machado ARDENGHI (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study aimed to explore the pathways that can influence cigarette smoking among adolescents. This population-based cohort followed a random sample of 12-year-old adolescents from southern Brazil for 6 years. Regular cigarette smoking was assessed through a self-reported question, previously used in the Brazilian National Survey of Scholar Health. We also gathered data on bullying, dental caries at baseline, incidence of caries, sex, friend network, and Sense of Coherence (SOC). Socioeconomic and demographic characteristics were also collected. Structural equation modeling was used to evaluate the pathways. Of the 1,134 adolescents examined at baseline, 768 were re-evaluated (67.7% retention rate). The prevalence of smoking was 37.6%. This prevalence was directly affected by low SOC (SC: -0.14, p < 0.01), low household income (SC: -0.12, p < 0.01), and male sex (SC: 0.15, p < 0.01). Presence of dental caries at baseline indirectly influenced the occurrence of dental bullying at follow-up via the incidence of dental caries (SC: 0.01, p < 0.05). Dental bullying indirectly influenced cigarettes consumption via SOC (SC: 0.62, p < 0.05). Friend network also indirectly influenced the consumption of cigarettes via SOC (SC: 0.32, p < 0.05). Psychosocial factors influence adolescent cigarette consumption through its higher direct and indirect effects (via bullying). In addition, behavioral, sociodemographic, and clinical factors also influence the occurrence of smoking.